1987
DOI: 10.1089/hyb.1987.6.111
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunodiagnosis of Human-Derived Squamous Cell Carcinoma

Abstract: Squamous cell carcinomas (SCC) of the head and neck are common and aggressive tumors. A murine IgG 2aK monoclonal antibody (A9) reactive with most SCCs was radiolabeled with I-131 and tested for localization and imaging ability in groups of nude mice bearing SCC tumors derived from two patients with head and neck cancer (UM-SCC-2 and UM-SCC-11B). The mice also received I-125 labeled isotype-matched control antibody UPC-10 for double-label counting. Animals were imaged at multiple time points post-injection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The attenuation values observed for the negative control samples that were targeted with gold nanorods (larynx and oral cancer cells targeted with nanorods that are coated with non matching antibodies, and normal fibroblast and melanoma cells targeted with A9 antibodies) revealed relatively low non-specific binding (58, 54, 50, 62 HU, respectively), and demonstrate that head and neck tumors may show a likely enhancement of 3-4 times the local contrast of non-targeted tissue in vivo . Such a specificity and local enhancement is consistent with a previous study investigating the potential use of UM-A9 as a radiolabeled imaging agent for human squamous carcinoma tumors in vivo 27. The attenuation value observed for the positive control sample, the bare gold nanorods, is 158 HU; this high number was expected since the sample contained a high concentration of gold (2.5 mg/mL).…”
Section: Ct Scanssupporting
confidence: 90%
See 2 more Smart Citations
“…The attenuation values observed for the negative control samples that were targeted with gold nanorods (larynx and oral cancer cells targeted with nanorods that are coated with non matching antibodies, and normal fibroblast and melanoma cells targeted with A9 antibodies) revealed relatively low non-specific binding (58, 54, 50, 62 HU, respectively), and demonstrate that head and neck tumors may show a likely enhancement of 3-4 times the local contrast of non-targeted tissue in vivo . Such a specificity and local enhancement is consistent with a previous study investigating the potential use of UM-A9 as a radiolabeled imaging agent for human squamous carcinoma tumors in vivo 27. The attenuation value observed for the positive control sample, the bare gold nanorods, is 158 HU; this high number was expected since the sample contained a high concentration of gold (2.5 mg/mL).…”
Section: Ct Scanssupporting
confidence: 90%
“…Previously it has been demonstrated that SCC is characterized by significant over-expression of the A9 antigen 24, which is also called the alpha6beta4 integrin 25, and that there is a strong correlation between the A9 expression level and metastatic behavior 26. It has also been demonstrated that the UM-A9 antibody can home onto SCC tumors in vivo 27. An additional reason for choosing head and neck cancer was because one of its major diagnostic challenges today is a reliable detection of involved lymph nodes, since their status is one of the most important prognosis predictors, and is also critical for appropriate treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas extensive studies using radiolabelled MAbs have been performed for ovarian or colorectal carcinomas (Colcher et al, 1988;Epenetos et al, 1986) there is only limited experience in the use of MAbs for detection of SCCs. Wahl et al (1987) used the A9 antibody with moderate success to image SCC xenografts, obtaining tumor to blood ratios of 1.84 at day 7 after i.v. injection.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies possibly suitable for radioimmunoimaging of head and neck squamous cell carcinoma exist already (12)(13)(14). Radioimmunodetection based on antibodies to retroviral-PI SE-related material might also be applicable to head and neck carcinomas, as these produce low molecular weight factors ( c 25 kDa), capable of inhibiting the chemotaxis of mononuclear phagocytes (27), the effect of which can be neutralized by antibodies to P15E.…”
Section: Discussionmentioning
confidence: 99%